McGraw-Hill dictionary of geology and mineralogy (McGraw-Hill, 1997)
This book contains 8.700 up-to-date entries that fully define the language of geology and mineralogy; it covers physical geology, historical geology, mineralogy, marine geology, plate tectonics, petrology, sedimentology, and stratigraphy. The book includes hundreds of synonyms, acronyms, and abbrviations. It also provides pronunciations for all terms. Finally there is appendix that contains tables of useful data and information